Application of The Philosophy of “Gotong Royong” To Improve Tax Compliance in Indonesia - Gita Arasy Harwida; Heru Tjaraka (Jurnal Reviu Akuntansi dan Keuangan, 2024)
Purpose: This research aims to offer the concept of gotong royong (mutual cooperation) in Indonesia as one of the factors that must be applied in order to improve tax compliance in Indonesia Methodology/approach: This study is a qualitative study with a library-research approach. Findings: Gotong royong, which means mutual cooperation, is a philosophy that has been ingrained in the Indonesian people; therefore, it should be an important component in carrying out counseling, socialization, and tax inclusion education for the Indonesian people. So, the perspective on tax obligations and compliance shifts from what was only an obligation to becoming a common necessity in building an independent and more sovereign Indonesian state. Practical implications: Theoretically, this research provides a new perspective on the application of social interaction theory and the theory of planned behavior, although the concepts offered in this article still require further study at the practical level. Originality/value: Research related to tax compliance has mostly been carried out using a quantitative survey approach or an empirical study approach. However, this research examines tax compliance from a different perspective, namely the philosophy of tax as a tool in developing the country, which is actually an embodiment of the local philosophy of Indonesia called gotong royong. To the best of the researchers' knowledge, this has not been widely implemented.